Effectiveness of Peppermint Aromatherapy in Reducing the Incidence of PONV in Post-Anesthesia Bone Patients - Fatimah Fatimah; Ikhsan Amran; Iswenti Novera; Yenni Elfira; Irwadi Irwadi; Futi Hanna A’la (GLOBAL HEALTH SCIENCE GROUP, 2025)
Post Operative Nausea and Vomiting (PONV) is a common complication after surgery with spinal anesthesia, with an incidence reaching 20–30%. PONV can prolong hospitalization, increase treatment costs, and reduce patient comfort. Peppermint aromatherapy is an effective, easy, and patient-accepted alternative to reduce PONV symptoms. Peppermint contains menthol which is carminative and antispasmodic, and can provide a relaxing effect through stimulation of the central nervous system. Objective to determine the effect of peppermint aromatherapy on the incidence of PONV in patients after spinal anesthesia. Method: This study was a quasi-experiment with a pre and post test design without control. Thirty post-spinal anesthesia patients were given peppermint aromatherapy, then PONV incidence was measured before and after the intervention using the Gordon scale. Data analysis used the Wilcoxon test. Results: Peppermint aromatherapy has been proven to be effective in reducing the incidence of PONV in patients after spinal anesthesia. Of the 30 respondents, the majority experienced nausea (73.3%) and vomiting (26.7%) before the intervention. After aromatherapy, 36.7% did not experience symptoms, and only 6.7% still vomited. The Wilcoxon test showed a significant difference (p = 0.000), indicating that peppermint aromatherapy was statistically effective in reducing PONV. Conclusions: Peppermint aromatherapy is effective in reducing the incidence of PONV in post-spinal anesthesia patients, as indicated by a decrease in nausea and vomiting symptoms after the intervention.